Using the Elzaki Transform to solve systems of partial differential equations (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
In this research, we applied Elzaki transform to obtain the general formulas of solution for a system of partial differential equations with constant coefficients in dimension two. After that, these formulas used for solving some system, whether they are homogeneous or non-homogeneous